2008
DOI: 10.1002/eji.200737800
|View full text |Cite|
|
Sign up to set email alerts
|

CD137 ligand reverse signaling has multiple functions in human dendritic cells during an adaptive immune response

Abstract: T cell activation via dendritic cells (DC) is an important step in the adaptive immune response, which requires DC maturation, migration to lymph nodes and presentation of antigen to T cells. CD137 receptor expressed on activated T cells is a potent costimulatory molecule. Here, we investigated the functions of CD137 ligand (CD137L) in human monocyte-derived DC during an immune response. Cross-linking of CD137L on DC leads to cell maturation in an autocrine fashion, mostly via release of TNF-a. Reverse signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
58
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 36 publications
1
58
0
1
Order By: Relevance
“…On the other hand, others showed that CD137L ligation enhances proliferation of hematopietic progenitor cells and its differentiation to monocytes, macrophages [34,35]. Reverse signals of CD137L enhances DC maturation and subsequent antigen-specific T-cell differentiation [36]. These together with previous studies using transgenic mice, knockout mice or mice injected with anti-CD137L Ab [19,37,38] clearly show potential in vivo effects of CD137L on innate immunity, although there are some discrepancies in the effects of CD137L.…”
Section: Discussionmentioning
confidence: 77%
“…On the other hand, others showed that CD137L ligation enhances proliferation of hematopietic progenitor cells and its differentiation to monocytes, macrophages [34,35]. Reverse signals of CD137L enhances DC maturation and subsequent antigen-specific T-cell differentiation [36]. These together with previous studies using transgenic mice, knockout mice or mice injected with anti-CD137L Ab [19,37,38] clearly show potential in vivo effects of CD137L on innate immunity, although there are some discrepancies in the effects of CD137L.…”
Section: Discussionmentioning
confidence: 77%
“…2). In this scenario, the interaction of CD137L + B cells with CD137 + B cells might bidirectionally costimulate B cells and mediate cell functional changes, because CD137L can also transduce signals in certain cell types (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, prominent phenotypic changes in monocytes/macrophages follow CD137L stimulation, such as cell proliferation, production of pro-inflammatory cytokines and chemokines, and up-regulation of cell adhesion molecules, thus enhancing the inflammatory response in an autocrine or paracrine fashion (reviewed in Shao and Schwarz, 2011). CD137L signaling mediates similar activities in dendritic cells that are observable in monocytes/ macrophages: cross-linking CD137L enhances the expression of co-stimulatory ligands and MHC molecules and cytokine release (Lippert et al, 2008). Deficient CD137L signaling induces myelopoiesis (Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%